Anti-ultraviolet para-aramid fiber and production process thereof
Through the UV para-aramid fiber production process, anti-UV aging agent and ultrasonic treatment, the problems of reduced strength and insufficient water absorption under ultraviolet light are solved, and efficient anti-UV performance and moisture absorption and quick drying effect are achieved. Broaden the application scope of products.
Patent Information
- Application Number
- CN202411057959.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-02
- Publication Date
- 2025-01-10
AI Technical Summary
Aramid fibers are prone to breaking amide bonds after ultraviolet irradiation, reducing fiber strength and increasing brittleness. At the same time, they are low in water absorption and poor moisture permeability, which limits their application range.
Using a UV para-aramid fiber production process, the spinning slurry is prepared by using sulfuric acid at a concentration of more than 100%, defoaming, filtering, spinning to form fibers, and ultrasonic treatment is carried out in the anti-UV aging agent impregnation liquid. Combined with suitable drying conditions, cross-shaped para-aramid fibers with ultraviolet resistance are produced.
It improves the UV resistance and moisture absorption and quick drying effect of the fiber, enhances the physical and mechanical properties of the fiber, reduces production costs, and meets the requirements of green processing and manufacturing.
Smart Images

Figure CN119287547A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of aramid production, and in particular relates to an anti-ultraviolet para-aramid fiber and a production process thereof. Background Art
[0002] Aramid, the full name of "aromatic polyamide fiber", is mainly divided into two types: one is meta-aramid with a zigzag molecular chain arrangement; the other is para-aramid with a linear molecular chain arrangement. The special molecular structure of aramid fiber gives it many excellent properties, including good mechanical properties, excellent flame retardancy, heat resistance, stable chemical properties, durability, radiation resistance, etc. It has broad application prospects in aerospace, national defense, military industry, rail transportation and other fields.
[0003] The cross-sectional fiber shape characteristics can make up for the shortcomings of circular cross-sectional fibers in torsional strength, roughness, elasticity, appearance, etc. The "cross" aramid fiber has a large specific surface area and numerous micropores or grooves on the surface, which can achieve the effect of rapid water absorption, diffusion and volatilization.
[0004] Aromatic polyamide fibers are very sensitive to ultraviolet rays. Their molecular chains contain a large number of unsaturated chromophores (amide bonds, benzene rings). Under the combined action of ultraviolet rays and oxygen, the CN bonds of the -CONH- groups inside the fibers break and oxidize to form -COOH-. The tensile cross-section of the aramid fiber changes from a fibril-like split section to a flat section, which accelerates the oxidative degradation of the polymer chain, destroys the regular structure of the polymer chain, and reduces the physical and mechanical properties of the fiber. Therefore, it is necessary to explore a method for producing UV-resistant para-aramid fibers in order to develop functional aramid fibers and broaden the application range of the product. Summary of the invention
[0005] In order to overcome the problem that after aramid fiber is irradiated with ultraviolet light, some chromophores inside the fiber easily absorb ultraviolet radiation, resulting in the rupture of amide bonds, which reduces the fiber strength and increases brittleness, and the problem that aramid fiber has low water absorption and poor moisture permeability, the present invention provides an anti-ultraviolet para-aramid fiber and a production process thereof.
[0006] Based on the above purpose, the present invention adopts the following technical solutions:
[0007] A production process of UV-resistant para-aramid fiber, the process is as follows:
[0008] (1) preparing a spinning slurry with the dried PPTA resin using sulfuric acid having a concentration of more than 100%, wherein the concentration of the polymer in the obtained spinning slurry is 18 to 20 wt%;
[0009] (2) The spinning slurry is degassed in a degassing tank at 80-90°C for 0.5h-1.5h, filtered through a filter and then distributed into each branch pipe. The branch pipe distributes the spinning slurry to the corresponding pipeline and then sends it to the spinning metering pump. After passing through the cross-shaped spinneret holes of the spinneret, the extruded fibers are cooled, stretched, thinned and oriented in the air layer, and then passed through a coagulation bath to precipitate the residual sulfuric acid in the fibers, cooled, coagulated to form para-aramid fibers;
[0010] (3) washing the para-aramid fiber obtained in step (2) with pure water at 20-40° C. until the sulfuric acid content in the washing wastewater is less than 0.2 wt %, and drying the washed para-aramid fiber at 110-130° C. until the fiber moisture content is less than 10%, thereby obtaining para-aramid fiber;
[0011] (4) dissolving the anti-ultraviolet aging agent and the penetrant in deionized water to prepare an anti-ultraviolet aging agent impregnation solution, wherein the anti-ultraviolet aging agent accounts for 1-10% of the total mass, the penetrant accounts for 1-3% of the total mass, and the deionized water accounts for 89-97% of the total mass;
[0012] (5) immersing the prepared para-aramid fiber in an anti-ultraviolet aging agent impregnation solution and subjecting the fiber to ultrasonic treatment at 10-50° C. for 3-10 min;
[0013] (6) Drying the para-aramid fiber obtained in step (5) at 140-160° C. until the fiber moisture content is ≤10%, thereby obtaining an anti-ultraviolet para-aramid fiber.
[0014] Preferably, in step (1), the moisture content of the dried resin PPTA is ≤0.5%.
[0015] Preferably, in step (2), the spinning slurry temperature passing through the cross-shaped spinneret of the spinneret is 60-100°C, the air layer height is 3-15mm, the coagulation bath temperature is 5-25°C, and the coagulation bath mass fraction is 5-15%. The fiber running speed after extrusion is 300-350m / min.
[0016] Preferably, in step (5), the anti-ultraviolet aging agent is one or a mixture of any proportion of two or more of nano-TiO2, nano-ZnO, graphene oxide, soluble polyimide and nano-SiO2.
[0017] Preferably, in step (5), the penetrant is fatty alcohol polyoxyethylene ether.
[0018] Preferably, in step (5), the temperature of the anti-ultraviolet aging agent impregnation liquid is 10-50°C.
[0019] Preferably, in step (5), the ultrasonic frequency is 20-20000 Hz.
[0020] The present invention also provides anti-ultraviolet para-aramid fiber produced by the above process.
[0021] Compared with conventional para-aramid fibers, the present invention has the following advantages and effects:
[0022] (1) Cross-section fiber: As a functional fiber, its shape characteristics can make up for the shortcomings of round fibers in terms of roughness, elasticity and other properties. Cross-shaped para-aramid fiber has a large specific surface area and numerous micropores or grooves on the surface, which can achieve the effect of rapid water absorption, diffusion and volatilization. It can quickly release sweat and moisture on the skin surface to the outside and evaporate quickly, keeping the fabric surface dry.
[0023] (2) Anti-ultraviolet: The present invention uses an anti-ultraviolet aging agent to treat para-aramid fiber. The present invention uses para-aramid fiber as the main material and uses the anti-ultraviolet aging agent to block ultraviolet rays outside the fabric through refraction and reflection or has a strong absorption effect on ultraviolet light, thereby enabling the para-aramid fiber to obtain anti-ultraviolet function.
[0024] (3) Economic and environmentally friendly: The present invention uses para-aramid fiber, anti-ultraviolet aging agent, etc. as main materials, and adopts the impregnation method to perform anti-ultraviolet finishing on the para-aramid fiber. The para-aramid fiber has the function of moisture absorption and quick drying, and also has the function of anti-ultraviolet, thereby reducing the production cost. In addition, the process is simple, the operation is simple, the anti-ultraviolet effect is good, the product quality is stable, and the processing process meets the requirements of green processing and manufacturing. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is the structure of a cross-hole spinneret.
[0026] Figure 2 The invention discloses a production process of UV-resistant para-aramid fiber. DETAILED DESCRIPTION
[0027] The present invention is further described below with reference to examples, but the scope of protection claimed by the present invention is not limited to the scope represented by the examples.
[0028] Embodiment 1:
[0029] A production process for producing UV-resistant para-aramid fibers, such as Figure 2 As shown, the process is as follows:
[0030] (1) The dried PPTA resin (water content ≤ 0.5%) was used to prepare a spinning slurry with 100.1% sulfuric acid. The concentration of the polymer in the obtained spinning slurry was 18.7 wt%.
[0031] (2) The spinning slurry is degassed in a degassing tank at 81°C for 1 hour, filtered through a filter, and then divided into branch pipes. The branch pipes distribute the spinning slurry to the pipelines and then send it to the spinning metering pump. Figure 1 After passing through the cross-shaped spinneret holes (lateral width: 0.0011 mm, longitudinal width: 0.0011 mm, lateral length: 0.012 mm, longitudinal length: 0.013 mm) of the spinneret shown in the figure, the extruded fibers are cooled, stretched, thinned and oriented in an air layer with a height of 9 mm at a running speed of 350 m / min, and then passed through a coagulation bath at a temperature of 10°C to precipitate the residual sulfuric acid in the fibers, and then cooled and coagulated to form fibers. The mass fraction of the coagulation bath is 10% (referring to the mass fraction of sulfuric acid in the coagulation bath, the same below).
[0032] (3) washing the fiber obtained in step (2) with pure water at 30° C. until the sulfuric acid content in the washing wastewater is less than 0.2 wt %. The washed para-aramid fiber is dried at 120° C. until the fiber moisture content is ≤10%, thereby obtaining para-aramid fiber;
[0033] (4) Preparation of anti-ultraviolet aging agent impregnation solution: Add nano-TiO2 (anti-ultraviolet aging agent) and fatty alcohol polyoxyethylene ether (penetrant) into deionized water, wherein nano-TiO2 accounts for 4% of the total mass, fatty alcohol polyoxyethylene ether accounts for 2% of the total mass, and deionized water accounts for 94% of the total mass.
[0034] (5) The prepared para-aramid fiber is immersed in an anti-ultraviolet aging agent impregnation solution, and is subjected to ultrasonic treatment at 40 kHz for 5 minutes at a treatment temperature of 30° C. to promote the diffusion of the anti-ultraviolet aging agent into the fiber.
[0035] (6) The anti-ultraviolet treated para-aramid fiber is dried at 150° C. until the fiber moisture content is ≤10%, thereby obtaining the anti-ultraviolet para-aramid fiber.
[0036] Para-aramid fiber is produced by cross-section, and the impregnation method is adopted with anti-ultraviolet aging agent, so that the para-aramid fiber can obtain the effect of moisture absorption and quick drying, and also obtain the anti-ultraviolet function. The process parameters in the spinning process affect the fiber forming process. The appropriate spinning temperature can enhance the spinnability of the fiber and obtain ideal physical and mechanical properties. When the spinning temperature is too high, it will accelerate the degradation of the polymer in the spinning slurry, resulting in a decrease in viscosity, causing the pressure fluctuation of the metering pump to affect the spinnability of the fiber; when the spinning temperature is too low, the flow viscosity of the spinning slurry is too high, and the shear stress in the spinneret hole increases, reducing the spinnability. Therefore, it is necessary to explore the effect of spinning temperature on anti-ultraviolet para-aramid fiber.
[0037] According to GB / T 14344-2008 “Test method for tensile properties of chemical fiber filaments” and GB / T 18830-2009 “Evaluation of UV protection performance of textiles”, the properties of UV-resistant para-aramid fibers at different spinning temperatures are shown in Table 1.
[0038] Table 1 Effect of spinning temperature on the properties of UV-resistant para-aramid
[0039]
[0040] It can be seen from Table 1 that as the spinning temperature increases, the viscosity of the spinning slurry decreases, the cross-sectional integrity of the para-aramid fiber decreases, and the spinnability deteriorates. Under comprehensive conditions, the spinning temperature is most preferably 80-90°C.
[0041] Embodiment 2:
[0042] The air layer height is an important parameter affecting the dry-jet-wet spinning process. It enables the scattered liquid crystal molecular chains in the spinning slurry to further elongate and orient along the fiber axis through tensile flow, thereby allowing the primary fibers to form a highly crystalline and highly oriented fiber structure, giving the fibers excellent mechanical properties. Therefore, it is necessary to explore the effect of the air layer height on UV-resistant para-aramid fibers.
[0043] Process parameters: spinning temperature 80°C, air layer height 3-15mm, coagulation bath temperature 10°C, coagulation bath mass fraction 10%, anti-ultraviolet aging agent-nano TiO2 dosage 4wt%, anti-ultraviolet aging agent impregnation liquid temperature 30°C. The specific operation process is the same as in Example 1.
[0044] According to GB / T 14344-2008 “Test method for tensile properties of chemical fiber filaments” and GB / T 18830-2009 “Evaluation of UV protection performance of textiles”, the performance of anti-UV para-aramid fiber at different air layer heights is measured and shown in Table 2.
[0045] Table 2 Effect of air layer height on the performance of para-aramid fiber against UV
[0046]
[0047] It can be seen from Table 2 that with the increase of the air layer height, the breaking strength of the UV-resistant para-aramid fiber increases slightly, and the cross-sectional integrity is better; but when the air layer height continues to increase, the mechanical properties of the spun fiber begin to decrease. Under comprehensive conditions, the preferred air layer height is most preferably 9-12 mm.
[0048] Embodiment 3:
[0049] The coagulation bath temperature will affect the double diffusion between the spinning slurry and the coagulation bath, thereby affecting the orientation structure inside the nascent fiber. Therefore, it is necessary to explore the effect of the coagulation bath temperature on UV-resistant para-aramid fibers.
[0050] Process parameters: spinning temperature 80°C, air layer height 9mm, coagulation bath temperature 5-25°C, coagulation bath mass fraction 10%, anti-ultraviolet aging agent-nano TiO2 dosage 4wt%, anti-ultraviolet aging agent impregnation liquid temperature 30°C. The specific operation process is the same as in Example 1.
[0051] According to GB / T 14344-2008 “Test method for tensile properties of chemical fiber filaments” and GB / T 18830-2009 “Evaluation of UV protection performance of textiles”, the performance of UV-resistant para-aramid fiber at different coagulation bath temperatures is shown in Table 3.
[0052] Table 3 Effect of coagulation bath temperature on the performance of anti-ultraviolet para-aramid
[0053]
[0054] It can be seen from Table 3 that with the increase of the coagulation bath temperature, the breaking strength of the UV-resistant para-aramid fiber increases slightly, and the cross-sectional integrity is better; but when the coagulation bath temperature continues to increase, the mechanical properties of the spun fiber decrease. Under comprehensive conditions, the coagulation bath temperature is preferably 10-15°C.
[0055] Embodiment 4:
[0056] The content of sulfuric acid in the coagulation bath will affect the rate of double diffusion between the spinning slurry and the coagulation bath, thereby affecting the liquid crystal structure inside the nascent fiber. Therefore, it is necessary to explore the effect of the mass fraction of the coagulation bath on UV-resistant para-aramid fibers.
[0057] Process parameters: spinning temperature 80°C, air layer height 9mm, coagulation bath temperature 10°C, coagulation bath mass fraction 0-20%, anti-ultraviolet aging agent-nano TiO2 dosage 4wt%, anti-ultraviolet aging agent impregnation liquid temperature 30°C. The specific operation process is the same as in Example 1.
[0058] According to GB / T 14344-2008 “Test method for tensile properties of chemical fiber filaments” and GB / T 18830-2009 “Evaluation of UV protection performance of textiles”, the properties of UV-resistant para-aramid fibers at different mass fractions of coagulation bath are shown in Table 4.
[0059] Table 4 Effect of coagulation bath mass fraction on the properties of UV-resistant para-aramid
[0060]
[0061] It can be seen from Table 4 that with the increase of the mass fraction of the coagulation bath, the breaking strength of the UV-resistant para-aramid fiber increases slightly, and the cross-sectional integrity is better; but when the mass fraction of the coagulation bath continues to increase, the mechanical properties of the spun fiber decrease. Under comprehensive conditions, the mass fraction of the coagulation bath is preferably 5-10%.
[0062] Embodiment 5:
[0063] Due to its special polymer chain composition and structure, para-aramid fiber will change its polymer chain chemical composition and break its chemical bonds after being irradiated by ultraviolet light. Therefore, it is necessary to explore the effect of the dosage of anti-UV aging agent on UV-resistant para-aramid fiber.
[0064] Process parameters: spinning temperature 80°C, air layer height 9mm, coagulation bath temperature 10°C, coagulation bath mass fraction 10%, anti-ultraviolet aging agent-nano TiO2 dosage 2-10%, anti-ultraviolet aging agent impregnation liquid temperature 30°C. The specific operation process is the same as in Example 1.
[0065] According to GB / T 14344-2008 “Test method for tensile properties of chemical fiber filaments” and GB / T 18830-2009 “Evaluation of UV protection performance of textiles”, the performance of UV-resistant para-aramid fiber at different dosages of anti-UV aging agent is shown in Table 5.
[0066] Table 5 Effect of the dosage of anti-ultraviolet aging agent on the performance of anti-ultraviolet para-aramid
[0067]
[0068] It can be seen from Table 5 that with the increase in the amount of anti-ultraviolet aging agent, the breaking strength of the anti-ultraviolet para-aramid fiber increases slightly, and the cross-sectional integrity is better; but when the amount of anti-ultraviolet aging agent continues to increase, the mechanical properties of the spun fiber decrease. Under comprehensive circumstances, the preferred amount of anti-ultraviolet aging agent is most preferably 4-6%.
[0069] Embodiment 6:
[0070] The temperature of the anti-UV aging agent impregnation solution is crucial for anti-UV finishing. As the temperature changes, the degree of reaction is different. Therefore, it is necessary to explore the effect of the temperature of the anti-UV aging agent impregnation solution on anti-UV para-aramid fiber.
[0071] Process parameters: spinning temperature 80°C, air layer height 9mm, coagulation bath temperature 10°C, coagulation bath mass fraction 10%, anti-ultraviolet aging agent-nano TiO2 dosage 4wt%, anti-ultraviolet aging agent impregnation liquid temperature 10-50°C. The specific operation process is the same as in Example 1.
[0072] According to GB / T 14344-2008 “Test method for tensile properties of chemical fiber filaments”, the properties of anti-ultraviolet para-aramid fibers at different anti-ultraviolet aging agent immersion liquid temperatures are measured and shown in Table 6.
[0073] Table 6 Effect of the temperature of the anti-ultraviolet aging agent impregnation solution on the anti-ultraviolet properties of para-aramid
[0074]
[0075] It can be seen from Table 6 that with the increase of the temperature of the anti-ultraviolet aging agent impregnation solution, the breaking strength of the anti-ultraviolet para-aramid fiber increases slightly, and the cross-sectional integrity is better; but when the temperature of the anti-ultraviolet aging agent impregnation solution continues to increase, the mechanical properties of the spun fiber decrease. Under comprehensive conditions, the preferred temperature of the anti-ultraviolet aging agent impregnation solution is most preferably 20-30°C.
[0076] Embodiment 7:
[0077] Compare the properties of para-aramid fibers treated with different types of anti-ultraviolet aging agents.
[0078] The nano-TiO2 process parameters are as follows: spinning temperature 80°C, air layer height 9mm, coagulation bath temperature 10°C, coagulation bath mass fraction 10%, anti-ultraviolet aging agent is nano-TiO2, TiO2 dosage 4wt%, anti-ultraviolet aging agent immersion liquid temperature 30°C. The specific operation process is the same as in Example 1.
[0079] The nano ZnO process parameters are as follows: spinning temperature 80°C, air layer height 9mm, coagulation bath temperature 10°C, coagulation bath mass fraction 10%, anti-ultraviolet aging agent is nano ZnO, nano ZnO dosage 4wt%, anti-ultraviolet aging agent immersion liquid temperature 30°C. The specific operation process is the same as in Example 1.
[0080] The nano-SiO2 process parameters are as follows: spinning temperature 80°C, air layer height 9mm, coagulation bath temperature 10°C, coagulation bath mass fraction 10%, anti-ultraviolet aging agent is nano-SiO2, nano-SiO2 dosage 4wt%, anti-ultraviolet aging agent immersion liquid temperature 30°C. The specific operation process is the same as in Example 1.
[0081] The graphene oxide process parameters are as follows: spinning temperature 80° C., air layer height 9 mm, coagulation bath temperature 10° C., coagulation bath mass fraction 10%, anti-ultraviolet aging agent is graphene oxide, graphene oxide dosage 4wt%, anti-ultraviolet aging agent immersion liquid temperature 30° C. The specific operation process is the same as in Example 1.
[0082] The soluble polyimide process parameters are as follows: spinning temperature 80°C, air layer height 9mm, coagulation bath temperature 10°C, coagulation bath mass fraction 10%, anti-ultraviolet aging agent is soluble polyimide, soluble polyimide dosage 4wt%, anti-ultraviolet aging agent immersion liquid temperature 30°C. The specific operation process is the same as in Example 1.
[0083] According to GB / T 14344-2008 “Test method for tensile properties of chemical fiber filaments” and GB / T 18830-2009 “Evaluation of UV protection performance of textiles”, the treatment effects of different types of anti-ultraviolet aging agents are measured and shown in Table 7.
[0084] Table 7 Comparison of treatment effects of different anti-ultraviolet aging agents
[0085]
[0086] It can be seen from Table 7 that the use of nano-TiO2 as an anti-ultraviolet aging agent has the best anti-ultraviolet effect and the best mechanical properties of the fiber.
[0087] Embodiment 8:
[0088] Compare the performance of UV resistant para-aramid fibers with that of conventional para-aramid fibers.
[0089] The process parameters of anti-ultraviolet para-aramid fiber are as follows: spinning temperature 80°C, air layer height 9mm, coagulation bath temperature 10°C, coagulation bath mass fraction 10%, anti-ultraviolet aging agent-nano TiO2 dosage 4%, and anti-ultraviolet aging agent impregnation liquid temperature 30°C. The specific operation process is the same as in Example 1.
[0090] Conventional para-aramid fiber process parameters are: spinning temperature 80°C, air layer height 9mm, coagulation bath temperature 10°C, coagulation bath mass fraction 10%. The specific operation process is referred to steps (1) to (3) of Example 1.
[0091] The process parameters of the cross-shaped para-aramid fiber are as follows: spinning temperature 80°C, air layer height 9mm, coagulation bath temperature 10°C, and coagulation bath mass fraction 10%. The specific operation process is as follows: steps (1) to (3) of Example 1.
[0092] According to GB / T 14344-2008 “Test method for tensile properties of chemical fiber filaments” and GB / T 8427-2019 “Textiles - Tests for color fastness - Color fastness to artificial light: Xenon arc shading”, the fiber properties of the best process for UV-resistant para-aramid fiber and the best process for conventional para-aramid fiber are compared in Table 8.
[0093] Table 8 Comparison of fiber properties of UV-resistant para-aramid fiber process with conventional process
[0094] Fiber properties UV-resistant para-aramid fiber Conventional para-aramid fiber Cross-shaped para-aramid fiber Breaking strength (cN / dtex) 22.03 20.67 20.31 Elongation at break (%) 3.21 3.74 3.65 Initial modulus (cN / dtex) 703.46 689.73 683.26 Moisture regain (%) 6.2 4.5 6.3 Sunlight resistance level 4-5 3-4 3-4
[0095] It can be seen from Table 8 that the mechanical properties of the para-aramid fiber treated with the best process for anti-ultraviolet para-aramid fiber are significantly higher than those of the para-aramid fiber treated with the conventional process, and the moisture absorption performance of the cross-shaped aramid fiber is even better.
[0096] Embodiment 9:
[0097] Comparison of fiber properties of UV-resistant para-aramid fibers before and after UV irradiation.
[0098] The process parameters of anti-ultraviolet para-aramid fiber are as follows: spinning temperature 80°C, air layer height 9mm, coagulation bath temperature 10°C, coagulation bath mass fraction 10%, anti-ultraviolet aging agent-nano TiO2 dosage 4%, and anti-ultraviolet aging agent impregnation liquid temperature 30°C. The specific operation process is the same as in Example 1.
[0099] According to GB / T 14344-2008 “Test method for tensile properties of chemical fiber filaments” and GB / T 8427-2019 “Textiles - Tests for color fastness - Color fastness to artificial light: Xenon arc irradiation”, the fiber properties of UV-resistant para-aramid fiber before and after UV irradiation are compared in Table 9.
[0100] Table 9 Comparison of fiber properties of UV-resistant para-aramid fiber before and after UV irradiation
[0101] Fiber properties Before UV irradiation After 24h UV irradiation After 48h UV irradiation Breaking strength (cN / dtex) 22.03 21.98 21.43 Elongation at break (%) 3.21 3.30 3.38 Initial modulus (cN / dtex) 703.46 698.53 681.29 Sunlight resistance level 4-5 4-5 4-5
[0102] It can be seen from Table 9 that after the para-aramid fiber produced using the best process for anti-ultraviolet para-aramid fiber was exposed to ultraviolet light for 24 hours and 48 hours, the physical and mechanical properties of the fiber did not change significantly, and the fiber had excellent anti-ultraviolet performance.
[0103] In summary, the present invention has developed a method of impregnating a semi-finished para-aramid fiber into an impregnation liquid containing an anti-ultraviolet aging agent by an impregnation method, selecting an appropriate amount of the anti-ultraviolet aging agent, and impregnating the para-aramid fiber in the impregnation liquid of the anti-ultraviolet aging agent under the synergistic effect of ultrasonic waves, and then drying to obtain the anti-ultraviolet para-aramid fiber. The specific process is: spinning temperature 60-100°C, air layer height 3-15mm, coagulation bath temperature 5-25°C, coagulation bath mass fraction 0-20%, anti-ultraviolet aging agent-nano TiO2 dosage 2-10wt.%, anti-ultraviolet aging agent impregnation liquid temperature 10-50°C. According to GB / T 14344-2008 "Test method for tensile properties of chemical fiber filaments" and GB / T 18830-2009 "Evaluation of UV protection performance of textiles", the fiber properties of the best process for anti-UV para-aramid fiber and the best process for conventional para-aramid fiber were compared: the mechanical properties of the para-aramid fiber produced by the best process for anti-UV para-aramid fiber were significantly higher than those of the para-aramid fiber produced by the conventional process, and the fiber also had excellent hygroscopicity and UV resistance.
[0104] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A production process for UV-resistant para-aramid fiber, characterized in that: The process is as follows: (1) The dried resin PPTA is used to prepare a spinning slurry with sulfuric acid having a concentration of more than 100%, and the concentration of the polymer in the obtained spinning slurry is 18-20wt%; (2) The spinning slurry is degassed in a degassing tank at 80-90℃ for 0.5 h to 1.5 h, filtered through a filter and then divided into each branch pipe. The branch pipe distributes the spinning slurry to the corresponding pipeline and then sends it to the spinning metering pump. After passing through the cross-shaped spinneret holes of the spinneret, the extruded fiber is cooled, stretched, thinned and oriented in the air layer, and then passes through a coagulation bath to precipitate the residual sulfuric acid in the fiber, cool it, and coagulate it to form para-aramid fiber; (3) washing the para-aramid fiber obtained in step (2) with pure water at 20-40° C. until the sulfuric acid content in the washing wastewater is less than 0.2 wt %, and drying the washed para-aramid fiber at 110-130° C. until the fiber moisture content is ≤10%, thereby obtaining para-aramid fiber; (4) dissolving the anti-ultraviolet aging agent and the penetrant in deionized water to prepare an anti-ultraviolet aging agent impregnation solution, wherein the anti-ultraviolet aging agent accounts for 1-10% of the total mass, the penetrant accounts for 1-3% of the total mass, and the deionized water accounts for 89-97% of the total mass; (5) immersing the prepared para-aramid fiber in an anti-ultraviolet aging agent impregnation solution and subjecting the fiber to ultrasonic treatment at 10-50° C. for 3-10 min; (6) Drying the para-aramid fiber obtained in step (5) at 140-160° C. until the fiber moisture content is ≤10%, thereby obtaining an anti-ultraviolet para-aramid fiber.
2. The production process of the UV-resistant para-aramid fiber according to claim 1, characterized in that: In step (1), the moisture content of the dried resin PPTA is ≤0.5%.
3. The production process of the UV-resistant para-aramid fiber according to claim 1, characterized in that: In step (2), the temperature of the spinning slurry passing through the cross-shaped spinneret of the spinneret is 60-100° C., the air layer height is 3-15 mm, the coagulation bath temperature is 5-25° C., and the mass fraction of the coagulation bath is 5-15%.
4. The production process of the UV-resistant para-aramid fiber according to claim 1, characterized in that: In step (5), the anti-ultraviolet aging agent is one or a mixture of any proportion of nano-TiO2, nano-ZnO, graphene oxide, soluble polyimide and nano-SiO2.
5. The production process of the UV-resistant para-aramid fiber according to claim 1, characterized in that: In step (5), the penetrant is fatty alcohol polyoxyethylene ether.
6. The production process of the UV-resistant para-aramid fiber according to claim 1, characterized in that: In step (5), the temperature of the anti-ultraviolet aging agent impregnation liquid is 10-50°C.
7. The production process of the UV-resistant para-aramid fiber according to claim 1, characterized in that: In step (5), the ultrasonic frequency is 20-20000 Hz.
8. The UV-resistant para-aramid fiber obtained by the production process according to any one of claims 1 to 7.
Citation Information
Cited By
Anti-aging para-aramid fiber and preparation method thereof
CN120666460A